APOA1 mRNA Expression in Ovarian Serous Carcinoma Effusions Is a Marker of Longer Survival. (1st July 2014) - Stavnes, Helene Tuft; Nymoen, Dag André; Hetland Falkenthal, Thea E.; Kærn, Janne; Tropé, Claes G.; Davidson, Ben
Abstract: Objectives: We previously described the overexpression of APOA1 and GPX3 in ovarian/peritoneal serous carcinoma compared with breast carcinoma effusions using gene expression array analysis. The objective of the present study was to validate this finding and to analyze the association between these genes and clinicopathologic parameters, including survival, in advanced-stage ovarian serous carcinoma. Methods: APOA1 and GPX3 mRNA expression using quantitative reverse transcriptase polymerase chain reaction (qRT-PCR) was analyzed in 121 effusions (101 ovarian, 20 breast carcinomas) and 85 solid ovarian carcinoma specimens (43 primary carcinomas, 42 metastases). Results: APOA1 and GPX3 transcript levels were significantly higher in ovarian carcinoma at all anatomic sites compared with breast carcinoma effusions ( P < .001). GPX3 mRNA levels were significantly higher in primary carcinomas and solid metastases from patients who received neoadjuvant chemotherapy compared with chemo-naïve tumors ( P = .016). APOA1 and GPX3 mRNA levels in the entire effusion series were unrelated to clinicopathologic parameters. However, higher APOA1 mRNA levels in primary diagnosis pre-chemotherapy effusions were significantly related to better overall survival ( P = .045), a finding that retained its significance in Cox multivariate analysis ( P = .016). Conclusions: APOA1 and GPX3 mRNA levels on qRT-PCR effectively differentiate ovarian from breast carcinoma. APOA1 may be a novel prognostic marker in metastatic serous carcinoma.